MENIMBANG KESEIMBANGAN TKA DAN TKI: IMPLIKASI PUTUSAN MK TERHADAP UU CIPTA KERJA - KADIR, NAZWA (Ganec Swara, 2025)
This research aims to explore the balance between foreign workers and Indonesian workers in the context of the Job Creation Law, with a focus on realizing the Constitutional Court’s decision. The study utilizes a multi-perspective method, including literature analysis, normative juridical approach, case analysis, and qualitative descriptive method to understand the complexity of the issue.The results show that the Constitutional Court’s decision has increased attention to the protection of migrant workers and their regulation. However, there are still many challenges faced in implementing the new policy, such as administrative and supervisory aspects. Statistical analysis also shows that there is a significant relationship between the use of foreign workers and the poverty rate of migrant workers.The conclusion of this study recommends the need for effective coordination between the legislative, executive, and judicial institutions to provide a balanced working environment for both types of labor. In addition, it is important to implement education and training for migrant workers so that they are ready to compete with foreign workers in the modern world of work. The results of this study are expected to make a positive contribution to national labor policy making that is more inclusive and sustainable.